Eksistensi Konvensi sebagai Sumber dan Praktek Ketatanegaraan di Indonesia - Tri Suhendra Arbani (UIN Sunan Kalijaga Yogyakarta, 2016)
Constitutional convention is one means for evaluation and improvement of the Constitution. Thus it can be said that the constitutional convention has a very strong position in the Indonesian legal system. Constitutional convention is part of the unwritten constitutional law norms that serve complementary, menyempurkan or even change and declare void substance written Constitution (UUD 1945) as the highest legal norms in the Republic of Indonesia. The Convention is not merely a habit that dialakukan by officials pemrintah but actually the constitution is a form of constitution is not written that has the function as a source of Constitutional Law and as the practice of state within a state, it can be seen from the practice that has been done by the leaders of nations and agencies -state institutions. So the presence of the convention has been enrich knowledge in practice and a source of state administration as well as cover the weaknesses of a written constitution.